دور تطبيق اإلدار ة اإللكترونية في تطو ير األداء الوظيفي لدى أساتذة معاهد علوم وتقنيات النشاطات الب دنية والرياضية - benalouche adel (My University, 2024)
الملخص باللغة العربية: عنوان الدِّراسة: دور تطبيق الإدارة الإلكترونية في تطوير الأداء الوظيفي لدى أساتذة معاهد علوم وتقنيات النشاطات البدنية والرياضية دراسة ميدانية بمعاهد الشرق الجزائري مشكلة الدِّراسة: هل لتطبيق الإدارة الإلكترونية دور في تطوير الأداء الوظيفي لدى أساتذة معاهد علوم وتقنيات النشاطات البدنية والرياضية بالشرق الجزائري؟ تساؤلات الدِّراسة: 1- ما مستوى تطبيق الإدارة الإلكترونية بالمعاهد من وجهة نظر الأساتذة ؟ 2- هل توجد فروق ذات دلالة إحصائية في رؤية الأساتذة لمستوى تطبيق الإدارة الالكترونية بالمعاهد محل الدراسة تعزى للمتغيرات (السن، الدرجة العلمية، الشهادة، الخبرة، الوظيفة (إداري، غير إداري)، التخصص) عند مستوى الدلالة α= 0.05؟ 3- هل يسهم تطبيق الإدارة الإلكترونية بالمعاهد في وتطوير الأداء الوظيفي لدى الأساتذة؟ 4- هل توجد فروق ذات دلالة إحصائية في رؤية الأساتذة لدور تطبيق الإدارة الإلكترونية في تطوير الأداء الوظيفي لدى أساتذة المعاهد محل الدراسة تعزى للمتغيرات (السن، الدرجة العلمية، الشهادة، الخبرة، الوظيفة (إداري، غير إداري)، التخصص) عند مستوى الدلالة α= 0.05؟ فرضيات الدِّراسة: 1- مستوى تطبيق الإدارة الإلكترونية بالمعاهد متوسط من وجهة نظر الأساتذة. 2- لا توجد فروق ذات دلالة إحصائية في رؤية الأساتذة لمستوى تطبيق الإدارة الالكترونية بالمعاهد محل الدراسة تعزى للمتغيرات (السن، الدرجة العلمية، الشهادة، الخبرة، الوظيفة (إداري، غير إداري)، التخصص) عند مستوى الدلالة α= 0.05. 3- يسهم تطبيق الإدارة الإلكترونية بالمعاهد في وتطوير الأداء الوظيفي لدى الأساتذة. 4- لا توجد فروق ذات دلالة إحصائية في رؤية الأساتذة لدور تطبيق الإدارة الإلكترونية في تطوير الأداء الوظيفي لدى أساتذة المعاهد محل الدراسة تعزى للمتغيرات (السن، الدرجة العلمية، الشهادة، الخبرة، الوظيفة (إداري، غير إداري)، التخصص)عند مستوى الدلالة α= 0.05. المنهج المستخدم: إستخدم الباحث المنهج الوصفي التحليلي. عيًنة الدِّراسة: شملت الدراسة عينة عشوائية مكونة من (178) عضو هيئة تدريس بمعاهد الشرق الجزائري. أدوات الدِّراسة: إستمارة إستبيانية موجهة للأساتذة بمؤسسات التعليم الجامعي للأنشطة البدنية والرياضية بالشرق الجزائري. النتائج المتوصل إليها في الدِّراسة: - إلى أن مستوى تطبيق الإدارة الإلكترونية بمعاهد الشرق الجزائري جاء بدرجة تقدير كبيرة من وجهة نظر الأساتذة. - لا توجد فروق ذات دلالة إحصائية في رؤية الأساتذة لمستوى تطبيق الإدارة الالكترونية بالمعاهد محل الدراسة تعزى للمتغيرات (السن، الدرجة العلمية، الشهادة، الخبرة، الوظيفة (إداري، غير إداري)، التخصص) عند مستوى الدلالة α= 0.05. - يسهم تطبيق الإدارة الإلكترونية بالمعاهد في وتطوير الأداء الوظيفي لدى الأساتذة. - لا توجد فروق دالة إحصائيا في رؤية الأساتذة لتطبيق الإدارة الإلكترونية دور في تطوير الأداء الوظيفي لدى أساتذة المعاهد محل الدراسة من وجهة نظرهم تعزى للمتغيرات (الدرجة العلمية، الشهادة، الخبرة، الوظيفة (إداري،د غير إداري) ) عند مستوى الدلالة α= 0.05. - توجد فروق دالة إحصائيا في رؤية الأساتذة لتطبيق الإدارة الإلكترونية دور في تطوير الأداء الوظيفي لدى أساتذة المعاهد محل الدراسة من وجهة نظرهم تعزى للمتغيرات (السن، التخصص) عند مستوى الدلالةα= 0.05 ----------------------------------- الملخص باللغة الأنجليزية: Summary: Title of the study: The role of the application of electronic management in the development of the functionality of professors of institutes of science and techniques of physical and sports activities is a field study in institutes of science and techniques of physical and sports activities in the Algerian east . Study problem: Does the application of electronic management have a role in the development of the functionality of professors of institutes of science and techniques of physical and sports activities in the Algerian east? Study questions: 1- What is the level of application of electronic management in the institutes of science and techniques of physical and sports activities in the Algerian East from the viewpoint of professors ؟ 2- Are there statistically significant differences in the professors’ viewpoint of the level of application of electronic management in institutes of science and techniques of physical and sports activities attributable to the variables (age, academic degree, certificate, experience, job (administrative, non-administrative), specialization) at the significance level α = 0.05? 3- Does the application of electronic management in institutes of science and techniques of physical and sports activities contribute to the development of professors’ functionality? 4- Are there statistically significant differences in the professors’ viewpoint of the role of the application of electronic management in the development of professors’ functionality attributable to the variables (age, academic degree, certificate, experience, position (administrative, non-administrative), specialization) at the Significance level α = 0.05? Study hypotheses: 1- The level of application of electronic management in the institutes of science and techniques of physical and sports activities in the Algerian East is average from the viewpoint of professors. 2- There are no statistically significant differences in the professors ‘viewpoint of the level of application of electronic management in institutes of science and techniques of physical and sports activities attributable to the variables (age, academic degree, certificate, experience, job (administrative, non-administrative), specialization) at the significance level α = 0.05. 3- The application of electronic management in the institutes of science and techniques of physical and sports activities contributes to the development of professors’ functionality. 4- There are no statistically significant differences in the professors’ viewpoint of the role of the application of electronic management in the development of professors’ functionality attributable to the variables (age, academic degree, certificate, experience, position (administrative, non-administrative), specialization) at the Significance level α = 0.05. Method used: The researcher used the descriptive analytical method. Study sample: The study included a random sample consisting of (178) faculty members at institutes of science and techniques of physical and sports activities in the Algerian east. Study tools: A questionnaire addressed to the professors of institutes of science and techniques of physical and sports activities in Algerian east. Results of the study: - that the level of application of electronic management in institutes of science and techniques of physical and sports activities in Algerian east was highly appreciated from the viewpoint of professors. - There are no statistically significant differences in the professors’ viewpoint of the level of application of electronic management in institutes of science and techniques of physical and sports activities attributable to the variables (age, academic degree, certificate, experience, job (administrative, non-administrative), specialization) at the significance level α = 0.05 -The application of electronic management in the institutes of science and techniques of physical and sports activities contributes to the development of the professors functionality. - There are no statistically significant differences in the professors’ viewpoint of the role of the application of electronic management in institutes of science and techniques of physical and sports activities in the development of the professors functionality attributable to the variables (scientific degree, certificate, experience, job (administrative, non-administrative)) at the significance level α= 0.05. - There are statistically significant differences in the professors’ viewpoint that the application of electronic management has a role in institutes of science and techniques of physical and sports activities in the development of the professors functionality attributable to the variables (age, specialization) at the significance level α = 0.05. --------------------------------- الملخص بالغة الفرنسية: Résumé: Titre de l'étude: Le rôle de l'application de la gestion électronique dans le développement de la fonctionnalité des professeurs d'instituts de science et techniques d'activités physiques et sportives est une étude de terrain dans les instituts de science et techniques d'activités physiques et sportives dans l'est algérien . Problème d'étude: L'application de la gestion électronique a-t-elle un rôle dans le développement de la fonctionnalité des professeurs d'instituts de science et techniques d'activités physiques et sportives dans l'est algérien? Questions d'étude: 1-Quel est le niveau d'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives dans l'Est algérien du point de vue des professeurs ؟ 2- Y a-t-il des différences statistiquement significatives dans le point de vue des professeurs’ du niveau d'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives attribuables aux variables (âge, diplôme universitaire, certificat, expérience, emploi (administratif, non administratif), spécialisation) au niveau de signification α= 0.05? 3-L'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives contribue-t-elle au développement de la fonctionnalité des professeurs? 4- Y a-t-il des différences statistiquement significatives dans la vue des professeurs du rôle de l'application de la gestion électronique dans le développement de la fonctionnalité des professeurs attribuables aux variables (âge, diplôme universitaire, etc, certificat, expérience, emploi (administratif, non administratif), spécialisation) au niveau de signification α= 0.05? les hypothèses: 1-Le niveau d'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives dans l'Est algérien est moyen du point de vue des professeurs. 2- Il n'y a pas de différences statistiquement significatives dans la vue des professeurs du niveau d'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives attribuables aux variables (âge, diplôme universitaire, certificat, expérience, emploi (administratif, non administratif), spécialisation) au niveau de signification α= 0.05. 3- L'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives contribue au développement de la fonctionnalité des professeurs. 4- Il n'y a pas de différences statistiquement significatives dans le point de vue des professeurs du rôle de l'application de la gestion électronique dans le développement de la fonctionnalité des professeurs attribuable aux variables (âge, diplôme universitaire, certificat, expérience, emploi (administratif, non administratif), spécialisation) au niveau de signification α = 0,05. Méthode utilisée: Le chercheur a utilisé la méthode analytique descriptive. Échantillon d'étude: L’étude comprenait un échantillon aléatoire composé de (178) membres du corps professoral dans les instituts de science et techniques d'activités physiques et sportives dans l'est algérien. Outils d'étude: Un questionnaire adressé aux professeurs d'instituts de sciences et techniques d'activités physiques et sportives dans l'est algérien. Résultats de l'étude: -que le niveau d'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives dans l'est algérien a été très apprécié du point de vue des professeurs. - Il n'y a pas de différences statistiquement significatives dans le point de vue des professeurs du niveau d'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives attribuables aux variables (âge, diplôme universitaire, certificat, expérience, emploi (administratif, non administratif), spécialisation) au niveau de signification α= 0.05. - L'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives contribue au développement de la fonctionnalité des professeurs. - Il n'y a pas de différences statistiquement significatives dans le point de vue des professeurs du rôle de l'application de la gestion électronique dans les instituts de science et techniques d'activités physiques et sportives dans le développement de la fonctionnalité des professeurs attribuable aux variables (diplôme scientifique, certificat, expérience, emploi (administratif, non administratif)) au niveau de signification α= 0.05. - Il existe des différences statistiquement significatives dans le point de vue des professeurs que l'application de la gestion électronique a un rôle dans les instituts de science et techniques d'activités physiques et sportives dans le développement de la fonctionnalité des professeurs attribuable aux variables (âge, spécialisation) au niveau de signification α= 0.05.